PREVALENCE OF BRONCHIECTASIS IN COPD PATIENTS - Buklioska Ilievska, Daniela; Mickovski, Ivana; Neshovska, Radmila; Buklioska, Adriana; Trajkova, Vesna; Minov, Jordan; Stoleski, Sasho; Mijakoski, Dragan (My University, 2023)
Introduction - There is increasing recognition that radiological bronchiectasis is present in many patients with COPD. Computed tomography scan images have been used to identify different radiological COPD phenotypes based on the presence and severity of emphysema, bronchial wall thickening, and bronchiectasis. Bronchiectasis is defined as an abnormal dilation of the bronchi, usually as a result of chronic airway inflammation and/or infection. The prevalence of bronchiectasis in patients with COPD is high, especially in advanced stages, estimated prevalence varies from 4% to 50%. Methods - COPD patients underwent chest CT as part of their clinical assessment. Patients were included if COPD was diagnosed based on spirometry and clinical assessment and excluded if there was clinical bronchiectasis. Scoring was by a simplified system based on Smith (Thorax, 1996) and returned a score of 0 (no bronchiectasis), 1 (0–50% of bronchi involved), or 2 (50–100% of bronchi involved) for each lobe, with a total score of 12 including the lingula; emphysema, interstitial lung disease (ILD), or other pathology was noted. A total of 220 COPD patients (77.2% ex- or current smokers, 79.5% male) were consecutively enrolled. Results - Bronchiectasis was present in 54.5% of patients (score ≥2/12) and there was significant inter-observer correlation in the scoring (r=0.63, p<0.0001). Scores were highest in the lower lobes and lowest in the middle lobes (1.66 vs 0.86, p<0.000). Patients with widespread bronchiectasis (score ≥6/12) had a trend towards reduced bronchodilator reversibility (4% vs 9%, p=0.08) than those with limited bronchiectasis. Emphysema was present in 77.2% and ILD in 11.36%. The overall prevalence of emphysema was not different between patients with and without previous pulmonary tuberculosis (PTB) n=30 (13.63%), but in those with previous PTB, a higher number of subjects with middle (p=0.002) and lower (p=0.017) lobe emphysema, higher severity score (p=0.029), higher prevalence of panlobular emphysema (p=0.015), and more extensive centrilobular emphysema (p=0.036) were observed. Conclusions - In this study, we found a higher prevalence of bronchiectasis than previously reported which may reflect the heterogeneity of COPD patients in a general respiratory clinic. Radiological features of bronchial wall thickening and mild bronchiectasis were commonly seen and when widespread this may result in reduced bronchodilator reversibility; however, the presence of radiological bronchiectasis was not related to disease severity. COPD patients with previous PTB had unique features of bronchiectasis and emphysema on HRCT, which were associated with significant dyspnea and higher frequency of severe exacerbations.
Keywords: COPD; Bronchiectasis